Preparação e caracterização de redes metalorgânicas à base de térbio(III) montadas em superfícies de poli(tereftalato de etileno)-PET - Aline de Barros Souza (2019)
Metal-organic frameworks (MOFs) are a class of hybrid materials consisting of a coordination network containing potential voids and formed from metal ions or clusters interconnected by organic spacers (building blocks). This new class of compounds has become a target in the chemistry of materials, due to the diverse applications in the field of catalysis, luminescence, magnetism. The study of synthetic routes in the MOFs area has intensified, since the synthesis conditions interfere directly in the porosity, crystallinity and structure of the obtained products. Two routes were studied to produce MOFs based on terbium (III) and 1,4-benzenedicarboxylate connector, the first was carried out at room temperature and the second on hydrothermal conditions. The X-ray diffraction measurements by polycrystals to both samples corroborate with the structure determined by X-ray diffraction by single crystal described by Yaghi et al., that showed formula Tb2(BDC)3(H2O)4. The poly(ethylene terephthalate) (PET) surface hydrolysis study was carried out to provide the terephthalate groups used for surface-mounted metal-organic frameworks (SURMOFs) growth (PET-SURMOFs). The better hydrolysis condition was found for the sample submitted to a NaOH solution 10 mol L-1 for 5 hours. This hydrolysis condition was used during the development of SURMOFs called PETPLH- SURMOFs and PET20H-SURMOFs. The PET20H-SURMOFs showed X-ray diffraction patterns with peaks corresponding to MOF Tb2(BDC)3(H2O)4, described by Yaghi, proving the method efficiency used. The synthesis to obtain the PETPLH-SURMOFs was carried out by the layer-by-layer method and under hydrothermal conditions. An analysis of scanning electron microscopy, atomic force microscopy, X-ray diffraction and luminescence observation in UV light chamber ([lambda] = 254 nm) for PETPLH-SURMOFs showed that terbium(III) was coordinated to the available terephthalate ion on the surface of the previously hydrolyzed PET plate. Luminescence measurements were performed for the MOFs and PET20H-SURMOFs, observing electronic transitions that were assigned to the terbium ion (III) coupled to the antenna effect of the spacer ligands. The MOFs and PET20H-SURMOFs were submit to pore activation with solvent exchange and subsequent heating to evaluate the surface area. The adsorption / desorption measures of N2 at 77K revealed showed small areas compared to newer MOFs.